(untitled) (Research, Society and Development, 2022)
Spiropyrans are a sort of organic molecule, known for their unique photochromic properties that allow them to be used in several application areas. The irradiation with ultraviolet light induces a ring-opening reaction of the spiropyran structure, breaking a specific carbon-oxygen bond, which gives rise to the open form called merocyanine, making its reactivity easily detectable. The objective of this research was to carry out the synthesis, characterization and study of the isomerization of hydroxy-functional spiropyrans from the formation of new metal complexes. In this work, a spiropyran-like molecule was synthesized from the condensation reaction of methyleneinoline precursors and hydroxybenzaldehyde derivative. The structures were characterized by UV-Vis, Infrared and 1H NMR spectrometric techniques. The product, when exposed to UV light, was able to rearrange and break the C-O bond, producing the open form of merocyanine. Furthermore, the complexation of metal ions Ca2+, Fe2+ and Ni2+ with spiropyran in solution revealed interesting spectral changes, which are concentration dependent, forming the merocyanine structure. These results are interesting from the point of view of chemosensor applications for metal ions.